Clinical characteristics of adrenal insufficiency induced by pembrolizumab in non‐small‐cell lung cancer. Issue 5 (15th December 2022) - Kurokawa, Kana; Mitsuishi, Yoichiro; Shimada, Naoko; Ito, Naoaki; Ogiwara, Misa; Miura, Keita; Asao, Tetsuhiko; Ko, Ryo; Shukuya, Takehito; Shibayama, Rina; Goto, Hiromasa; Takahashi, Kazuhisa
Abstract: Background and Aim: Immune checkpoint inhibitors have significantly improved the clinical outcomes of many cancer types, but they induce a range of immune‐related adverse events (irAEs). Although adrenal insufficiency (AI) is a rare irAE, it can lead to serious consequences. This study aimed to determine the clinical features of patients with advanced non‐small‐cell lung cancer (NSCLC) who developed AI following pembrolizumab treatment. Methods: We retrospectively reviewed and analyzed the clinical data of all patients with NSCLC treated with pembrolizumab at Juntendo University Hospital from February 2017 to December 2020. The diagnosis of AI was established based on the Endocrine Emergency Guidance for the acute management of endocrine complications of checkpoint inhibitor therapy in the UK and the clinical practice guidelines of the Japan Endocrine Society. Result: AI was clinically suspected in 59 out of 186 patients treated with pembrolizumab, and 10 (5.4%) cases were confirmed. The symptoms included hyponatremia ( n  = 9), fatigue ( n  = 8), and loss of appetite ( n  = 6). All patients had low adrenocorticotropic hormone (ACTH) levels, and five patients were diagnosed with isolated ACTH deficiency. All patients completely recovered with corticosteroid replacement. The median time to onset of AI was 8.0 (range 3.8–15.2) months. The median progression‐free survival in these patients was 22.4 (95% confidence interval 11.2–not reached) months. Conclusion: The incidence of AI among patients treated with pembrolizumab is more frequent than previously reported. In addition, secondary AI, especially isolated ACTH deficiency, is a major form of AI induced by pembrolizumab. Abstract :